HUBUNGAN PENGETAHUAN TENTANG KESEHATAN REPRODUKSI REMAJA (KRR) DENGAN PEMELIHARAAN ORGAN REPRODUKSI PADA REMAJA KELAS XI SMAN I BADEGAN PONOROGO - Eliya Rohmah; Fitri Nur Jannah (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2016)
At the high school 1 Badegan claimed not to know about adolescent reproductivehealth, reproductive organs how to maintain the right to complain out whitish. Based oninterviews that researchers do against a class XI student at SMAN 1 Badegan ofPonorogo, amounting to 6 people on March 30, 2014, it was revealed that not understandabout adolescent reproductive health, including three students claimed that once giventhe socialization of doctors but is given to students XIII-grade student, class X and classXI only representative to follow.The purpose of this study was to determine the relationship of knowledge aboutadolescent reproductive health with the maintenance of the reproductive organs of femalestudents in class XI IPA. Type of analytical research with cross sectional approach. Thestudy was conducted in SMA N 1 Badegan in December 2014. The population in thisstudy were all students of class XI IPA SMAN 1 Badegan which amounts to 91, thenumber of samples of 74 female students with simple random sampling technique.Variable research is knowledge of adolescents on adolescent reproductive health(independent) and maintenance of the reproductive organs (dependent). Instrumentresearch using questionnaires. To analyze the relationship between the two variablesusing statistical test of Rank Spearmeant with a significance level of 0.05.Based on the results, knowledge of adolescents on adolescent reproductive healthmajority of respondents knowledgeable enough (55.4%) and maintenance of thereproductive organs largely sufficient (64.9%). Based on statistical test showed RankSpearmeant ρ = 0.015 with a significance level of 5%, so 0.015 <0.05 then the Hareceived means that there is a relationship of adolescent reproductive health knowledgewith the maintenance of the reproductive organs with a level of closeness of relationshipis 0,282, which means a low level of the relationship.From the results of these studies are expected to be able to make planning theschool to increase knowledge about adolescent reproductive health, includingmaintenance of the reproductive organs so that students can raise awareness to maintainappropriate reproductive health knowledge.